The life cycle of handicraft textile products and domestic tradition clothing, its processes and sustainability (ModaPalavra e-periódico, 2024)
The article presents a qualitative analysis of the life cycle of handcrafted textile products. The authors interviewed artisans from the region of Ipameri in Goiás and analyzed the life cycle using the model proposed by Fletcher. In the literature review it was found that several authors have published research on the sustainability of artisanal textile production in the world and also on the materials and processes used in the artisanal production of textiles in the interior of Brazil, but as far as we know the analysis of the life cycle of products produced in rural Brazil is unprecedented. The research is important for the historical record and also for encouraging the sustainable production of handcrafted textiles.In the research, the procedures and materials used in the production of textiles were revealed and systematized. The life cycle analysis was carried out in a qualitative way, showing the lowest environmental impact compared to the industrialized mode. The research shows the importance for the sustainability of handcrafted products in the environmental and social dimensions. Handcrafted products encourage a longer lasting use of the product by minimizing the use and disposal of materials and energy. Craft production can be an alternative to a more sustainable production model.
Keywords: artisanal textile production; textile sustainability; life cycle analysis